Excitation mechanism in the intracluster filaments surrounding the Brightest Cluster Galaxies. Issue Volume 15:Issue S359(2020) (March 2019) - Polles, Fiorella L.
Abstract: Multi-phase filamentary structures surrounding giant elliptical galaxies at the center of cool-core clusters, the Brightest Cluster Galaxies (BCGs), have been detected from optical to submillimeter wavelengths. The source of the ionisation in the filaments is still debated. Studying the excitation of these structures is key to our understanding of Active Galactic Nuclei (AGN) feedback in general, and more precisely of the impact of environmental and local effects on star formation. One possible contributor to the excitation of the filaments is the thermal radiation from the cooling of the hot plasma surrounding the BCGs, the so-called cooling flow.